Teaching and learning practice in nursing in the adult care process - Chaves, Emília Soares; Lúcio, Ingrid Martins Leite; Palmeira, Isaura Letícia Tavares; Fernandes, Ana Fátima Carvalho; Gurgel, Almerinda Holanda (Rev Rene, 2003)
This study having as an aim evaluating a discipline of a nursing undergraduate course, it was carried out in April and May of the year 2003. One observed six theoretical classes and one laboratory practice, on the discipline Nursing in the Adult Care Process. The data were categorized in: reality description, critical analysis of reality and collective construction. One verified that the pedagogical line adopted is traditional and that the student-teacher relationship is vertical. The teaching methodology and the evaluation system were not discussed. The pedagogical resourses were predominantly overhead projector and transparencies. The evaluation of the studied content followed the positivist view. In this context, one concluded that there is a dichotomy between the experience and ideas in the postgraduate and undergraduate courses. In order to change this reality it would be necessary a more effective connection between these two levels of study.